The Influence of Consumer Behavior and Product Quality on Consumer Decision Making in Selecting Dana as Financial Technology Mobile Payment Application - Agung Raya; Budi Rustandi Kartawinata (Almana : Jurnal Manajemen dan Bisnis, 2022)
As technology advances and becomes more sophisticated, consumer behavior patterns shift. The presence of such events stimulates diverse corporate industries to compete to develop innovation. Businesses in the field of financial technology also use it (Fintech). DANA is a mobile payment application that supports ATM cards for online purchases. Although DANA is a new program, it is capable of adapting fast to attract users. DANA has proven to be the third most popular app in Indonesia, with the most users and the most downloads. The goal of this research is to analyze the influence of customer behavior and product quality on the selection to use DANA as a mobile payment application. This type of research is quantitative by using descriptive data analysis techniques that use multiple linear hypothesis models with a total of 400 research samples. The results obtained from this study that consumer behavior and quality product have a significant and positive effect on partial (individual) decision making. As the results of simultaneous testing (collectively) on consumer behavior and product quality to consumer decision making in choosing DANA as a mobile payment application has a significant effect and the results are accepted.